2021
DOI: 10.3390/app112110132
|View full text |Cite
|
Sign up to set email alerts
|

AWEU-Net: An Attention-Aware Weight Excitation U-Net for Lung Nodule Segmentation

Abstract: Lung cancer is a deadly cancer that causes millions of deaths every year around the world. Accurate lung nodule detection and segmentation in computed tomography (CT) images is a vital step for diagnosing lung cancer early. Most existing systems face several challenges, such as the heterogeneity in CT images and variation in nodule size, shape, and location, which limit their accuracy. In an attempt to handle these challenges, this article proposes a fully automated deep learning framework that consists of lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In the study by Zhang et al a two-step U-Net CNN segmentation method was proposed for different types of lung nodes in computed tomography images, providing a similar coefficient for Dice (0.8623) in division algorithms [42]. Banu et al showed a fully automated deep-learning framework, including models of lung nodule detection and segmentation, and their results showed that their proposed model achieved a Dice score of 89.79% and 90.35%, and an intersection on the alliance of 82.34% and 83.21% [43]. On the other hand, Monkam et al showed that the overall performance of CNN models depended significantly on the number of convolution layers and the size of the patches, and also revealed that the CNN model with two layers of convolution could have the best performance with 88.28% accuracy, 0.87 AUC, 83.45% F score, and 83.82% sensitivity [44].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Zhang et al a two-step U-Net CNN segmentation method was proposed for different types of lung nodes in computed tomography images, providing a similar coefficient for Dice (0.8623) in division algorithms [42]. Banu et al showed a fully automated deep-learning framework, including models of lung nodule detection and segmentation, and their results showed that their proposed model achieved a Dice score of 89.79% and 90.35%, and an intersection on the alliance of 82.34% and 83.21% [43]. On the other hand, Monkam et al showed that the overall performance of CNN models depended significantly on the number of convolution layers and the size of the patches, and also revealed that the CNN model with two layers of convolution could have the best performance with 88.28% accuracy, 0.87 AUC, 83.45% F score, and 83.82% sensitivity [44].…”
Section: Discussionmentioning
confidence: 99%
“…In this table, three parameters, sensitivity, specificity, and accuracy, are used for evaluation purposes. The quantitative results showed that the purposed technique outperformed the U-Net [37], AWEU-Net [38], 2D U-Net [9], 2D Seg U Det [39], 3D FCN [40], 3D nodule R-CNN [41], 2D AE [42], 2D CNN [43], 2D LGAN [44], and 2D encoder-decoder [45]. The accuracy of purposed method was 99%, which is much better than the other listed methods, as shown in Table 2.…”
Section: Image Segmentationmentioning
confidence: 91%
“…In 2021, Banu et al [ 82 ] proposed an attention-aware weight excitation U-Net (AWEU-Net) architecture in CT images for lung nodule segmentation. The architecture contains two stages: lung nodule detection based on fine-tuned Faster R-CNN and lung nodule segmentation based on the U-Net with position attention-aware weight excitation (PAWE) and channel attention-aware weight excitation (CAWE).…”
Section: Lung Cancer Prediction Using Deep Learningmentioning
confidence: 99%